Implementasi Model Physics Independent Learning Untuk Meningkatkan Kemampuan Pemecahan Masalah Fisika Peserta Didik - Tiara Mustika Wardani*; Evendi Evendi; Mudatsir Mudatsir; Susanna Susanna (JIPI (Jurnal IPA dan Pembelajaran IPA), 2021)
Physics is a science that discusses every result of studying the answers to the question of causes, as well as natural phenomena that can occur. The most complex problem experienced by students is the lack of skills in solving physics problems for students. The low problem solving ability of students resulted in the ability to master the basic concepts of students. This study aimed to observe the escalation of problem solving skills after the implementation of the PIL learning model in physics at MAN 6 Aceh Besar. This research is included in the type of quasi-experimental research by designing a nonequivalent control group using 2 class samples as the experimental class and the control class. The population of this study was 64 students with 43 students participating in the study. Purposive sampling method was used in order to select the study sample. The collected data was analyzed using an independent-t test technique. This study observed that PIL learning models gave a positive impact to student autonomous learning and problem solving skills. The escalation of both variables was observed from the N-Gain score. On the problem solving skills, the control group reached 0.50 N-Gain score and the eksperimen group reached 0.79.